NEATH: II. N2H+ as a tracer of imminent star formation in quiescent high-density gas - Priestley, Felix; Clark, P C; Glover, Simon; Ragan, S E; Fehér, O; Prole, L R; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
Star formation activity in molecular clouds is often found to be correlated with the amount of material above a column density threshold of ∼1022 cm−2⁠. Attempts to connect this column density threshold to a volume density above which star formation can occur are limited by the fact that the volume density of gas is difficult to reliably measure from observations. We post-process hydrodynamical simulations of molecular clouds with a time-dependent chemical network, and investigate the connection between commonly observed molecular species and star formation activity. We find that many molecules widely assumed to specifically trace the dense, star-forming component of molecular clouds (e.g. HCN, HCO+, CS) actually also exist in substantial quantities in material only transiently enhanced in density, which will eventually return to a more diffuse state without forming any stars. By contrast, N2H+ only exists in detectable quantities above a volume density of ⁠, the point at which CO, which reacts destructively with N2H+, begins to deplete out of the gas phase on to grain surfaces. This density threshold for detectable quantities of N2H+ corresponds very closely to the volume density at which gas becomes irreversibly gravitationally bound in the simulations: the material traced by N2H+ never reverts to lower densities, and quiescent regions of molecular clouds with visible N2H+ emission are destined to eventually form stars. The N2H+ line intensity is likely to directly correlate with the star formation rate averaged over time-scales of around a Myr.
Im Text ist "2" tiefgestellt und "+" hochgestellt
Gesehen am 09.02.2024
Veröffentlicht: 10. Oktober 2023